Post Hoc Analysis of Serbian hotel ratings - Konjikusic, Snezana M; Starčević, Slađana; Mašić, Saša (Industrija, 2019)
The purpose of this paper is to present basic characteristics and highlight the differences between post hoc tests, as well as to show their application on concrete data of the research conducted. The said tests are applied on data obtained in the research which found evidence of 240 Serbian hotel ratings, given by their 71,700 guests. Each guest rated: cleanliness, comfort, location, facilities, staff, value for money, and free Wi-Fi in the hotel. A difference in ratings in relation to hotel category was observed and explained using several post hoc tests. The use of those tests is made much easier with the development of numerous statistical software packages. Therefore, clearly differentiating each of the tests allows one to select the most appropriate test in the research process, according to the type of data and research objectives.The paper presents the tests used when one-way analysis of variance, which is a method frequently used in statistical processing of experimental data, finds evidence of the existence of statistically significant differences in values of arithmetic mean in groups of data observed. The task of post hoc tests is to determine which group of data leads to the difference observed. Tests thus presented here are: the Fisher LSD, the Tukey HSD, the Bonferroni , the Newman-Keuls, the Dunnett and the Scheffé test.